Free Fibula Flap With Chimeric Skin Paddles: Technical Tips and Clinical Experience - Ersin Gur; Batuhan Sencan; Ahmet Bicer; Yigit Ozer Tiftikcioglu; Zeyyat Cuneyt Ozek (Journal of Craniofacial Surgery, 2026)
Introduction: Advanced tumors and trauma may cause composite oromandibular defects involving the mandible, intraoral mucosa, and skin. Although these defects involve multiple components, they can be reconstructed simultaneously with a single flap. The free fibula flap with chimeric skin paddles provides single-stage, appropriate three-dimensional reconstruction of challenging composite defects of the oromandibular region. The authors present our experience with free fibula flaps with chimeric skin paddles for composite oromandibular defects. Methods: Between 2013 and 2023, 26 patients (20 male and 6 female) underwent reconstruction with free fibula flaps with chimeric skin paddles. Gunshot injury was the cause in 3 patients. Excision of squamous cell carcinoma (SCC) was the cause in the remaining 23 patients. Patients’ ages ranged from 43 to 77 years. A two-team approach was used in all patients. Results: The length of the fibular bone ranged from 5 cm to 13 cm. The width of the undivided fibular skin paddle ranged from 4 cm to 12 cm, and its length ranged from 8 cm to 23 cm. One hematoma and 2 cases of wound dehiscence occurred as nonvascular complications. In 1 patient, venous occlusion occurred on postoperative day 1. In this patient, necrosis of a single skin island occurred, but the second skin island and the bone were successfully salvaged. The remaining patients did not experience any vascular problems. Conclusion: The free fibula flap with chimeric skin paddles is a versatile and useful reconstructive option for complex composite oromandibular defects.